2014
DOI: 10.1080/07391102.2014.952665
|View full text |Cite
|
Sign up to set email alerts
|

Distinct molecular features facilitating ice-binding mechanisms in hyperactive antifreeze proteins closely related to an Antarctic sea ice bacterium

Abstract: Antifreeze proteins or ice-binding proteins (IBPs) facilitate the survival of certain cellular organisms in freezing environment by inhibiting the growth of ice crystals in solution. Present study identifies orthologs of the IBP of Colwellia sp. SLW05, which were obtained from a wide range of taxa. Phylogenetic analysis on the basis of conserved regions (predicted as the 'ice-binding domain' [IBD]) present in all the orthologs, separates the bacterial and archaeal orthologs from that of the eukaryotes'. Corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Horizontal gene transfer studies indicated the strong selection pressure favoring independent evolution of the IBPs in some Antarctic microorganisms facilitates their adaptation and survivability to the adversities in their niche. 26 In this study, we investigate the molecular recognition mechanism and interactions of ColAFP in freezing and subfreezing marine water using coarse grained molecular dynamics simulation method.…”
Section: Introductionmentioning
confidence: 99%
“…Horizontal gene transfer studies indicated the strong selection pressure favoring independent evolution of the IBPs in some Antarctic microorganisms facilitates their adaptation and survivability to the adversities in their niche. 26 In this study, we investigate the molecular recognition mechanism and interactions of ColAFP in freezing and subfreezing marine water using coarse grained molecular dynamics simulation method.…”
Section: Introductionmentioning
confidence: 99%